Organizational Culture and Psychological Empowerment : Private Universities in India - Tandon, Pallavi; Mishra, Shikha; Khan, Nusrat (Prabandhan: Indian Journal of Management, 2021)
There has been plenty of research work done in the area of organizational culture and also in the area of empowerment. However, there are fewer studies on organizational culture and teachers’ psychological empowerment in private universities. Organizational culture refers to the set of values, norms, and beliefs in the organization to assist in its smooth and effective functioning. Psychological empowerment talks about the measurements of self-sufficiency, professional growth, position, self-efficacy, affect, and decision-making. This research aimed to find out the type of organizational culture followed in private universities and measure the impact of organizational culture on teachers’ psychological empowerment in private universities in the Delhi/NCR region. The nature of the research was descriptive ; 315 teachers were approached, out of which a total of 250 teachers completed the questionnaire with a response rate of 80%. For collecting the data, a structured questionnaire of organizational culture (OCAI) and psychological empowerment was used along with the demographic details. The results showed that the market culture was the most dominating culture in private universities. The results also indicated that there was a strong and positive relationship between organizational culture and psychological empowerment.